PTU-115 Timing of endoscopy and 30 day mortality in patients admitted with variceal haemorrhage. (June 2019) - Samani, Syazeddy; Kaur, Devinder; Li, Ka-kit
Abstract : Introduction: Variceal haemorrhage carries a high mortality and current UK guidelines recommend endoscopy within 24 hours of admission but this is based on low level of evidence. 1, 2, 3 The aim of this evaluation is to assess the association between timing of endoscopy with 30 day mortality in patients admitted with upper gastrointestinal variceal haemorrhage (UGVH). Methods: A total of 77 cases were retrospectively identified with a diagnosis of UGVH from the 1st of January 2017 to the 31st of December 2017 across three hospital sites in one UK NHS trust. 53 cases were analysed. Patients who did not present with acute UGVH on admission were excluded. Timing of endoscopy was defined as acute (0–12 hours), early (12–24 hours), delayed (>24hours) and calculated from time of admission to time of completion of endoscopy. Outcome measured was 30 day mortality. Fisher's exact test was used for statistical analysis (p<0.05 defined as statistically significant). Results: The mean age of this cohort was 60.5 years old with 62.3% (n=33) male and 37.7% (n= 20) female. Mean and median shock index (SI) at time of presentation were 0.81 and 0.8 (IQR 0.6–0.9) respectively. 73.6% (n=39) had procedures performed within 24 hours. 34% (n=18) had acute endoscopy, 39.6% (n=21) had early endoscopy and 26.4% (n=14) had delayed endoscopy. The mean SI for those who had acute endoscopy was highest (0.89) compared to the early (0.78) and delayed endoscopy (0.76) group with mean UKELD scores of 51.6, 52 and 52.5 respectively. Overall 30 day mortality was 15.1% (n=8). Mortality rates between each group were as follows: 1) Acute endoscopy- 5.6% (n=1), 2) Early endoscopy- 19% (n=4), 3) Delayed endoscopy- 21.4% (n=3). Statistical analysis showed no association between the different groups and 30 day mortality (acute vs early p=0.3849, acute vs delay p=0.3377). Conclusion: Mortality rate was lowest in the acute endoscopy group although statistical analysis suggested no significant association between timing of endoscopy and 30 day mortality. One may argue potential benefits of acute endoscopy based on the higher mean SI indicating greater mortality risk but a bigger, prospective multi-centre study is required to show the optimal timing and impact that timing of endoscopy may have on mortality for this cohort. Reference: Chen PH, Chen WC, Hou MC, et al. Delayed endoscopy increases re-bleeding and mortality in patients with hematemesis and active esophageal variceal bleeding: a cohort study. J Hepatol 2012;57:1207–13. Dhiraj Tripathi, Adrian J Staley, Peter C Hayes, et al . UK guidelines on the management of variceal haemorrhage in cirrhotic patients. Gut 2015;0:1–25. NICE CG141 - Acute upper gastrointestinal bleeding in over 16s: management